PERUBATAN MELAYU TRADISIONAL: KITAB TIBB PONTIANAK (Malay Traditional Medicine: Kitab Tibb Pontianak) - Abdul Hamid, Faisal@Ahmad Faisal; Fauzi, Nurul Wahidah (Journal of Al-Tamaddun, 2012)
The importance of the study of Malay manuscripts predicate of an effort to understand the wisdom, history, culture, life, experience and world view of the Malay community. Many Malay manuscripts written in the form of extended knowledge. In the manuscripts text, it is full of guidance, advice, entertainment, education, history, politics, international relations, medicine, science, technology and much more information and knowledge. These include traditional Malay medicine practice. Therefore, this study will examine the traditional Malay medicine practice in the book of Tibb Pontianak.